2015
DOI: 10.1148/radiol.2015142690
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-based Contrast Agent Accumulates in the Brain Even in Subjects without Severe Renal Dysfunction: Evaluation of Autopsy Brain Specimens with Inductively Coupled Plasma Mass Spectroscopy

Abstract: Even in subjects without severe renal dysfunction, GBCA administration causes gadolinium accumulation in the brain, especially in the DN and GP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
579
3
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 788 publications
(614 citation statements)
references
References 16 publications
25
579
3
7
Order By: Relevance
“…Gadolinium presence was originally observed in bone [5,6,30] and more recently in the brain [7][8][9][31][32][33][34][35][36][37][38][39] in patients with normal renal function.…”
Section: Gadolinium Storage Conditionmentioning
confidence: 98%
See 2 more Smart Citations
“…Gadolinium presence was originally observed in bone [5,6,30] and more recently in the brain [7][8][9][31][32][33][34][35][36][37][38][39] in patients with normal renal function.…”
Section: Gadolinium Storage Conditionmentioning
confidence: 98%
“…The authors found proportionate content of brain and bone, with bone having approximately 20 times the concentration of gadolinium compared to brain, with both linear and macrocyclic agents [9]. What is currently known, is that gadolinium is retained in body tissues, regardless of renal function or even GBCA stability [5][6][7][8][9]. Higher concentrations appear to occur in patients with renal impairment [40] or after exposure to the less stable GBCAs [41,42].…”
Section: Gadolinium Storage Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in the chemical structure of the ligands explain the difference in thermodynamic and kinetic stability, whereby the non-ionic linear chelates are the least stable and the ionic macrocyclic chelates are the most stable [3]. The free gadolinium ion is mostly hydrated in biological systems, and this Gd(H 2 O) 8 3+ ion is toxic because of its chemical similarities to Ca 2+ , which is an important factor for proper functioning of many processes in the human body such as contraction of the heart muscle and smooth muscle cells, and nerve transmission. Gd 3+ can compete with Ca 2+ due to its similarity in ion radius, and could thereby disturb physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Gadolinium deposition in brain tissue and its relation to T1 signal intensity changes was confirmed by histopathological human studies [10][11][12][13]. However, these studies found that gadolinium deposits were present in all evaluated brain tissues (with higher concentration in DN followed by GP) after the administration of either linear or macrocyclic agents, suggesting that MRI has a relative limited sensitivity to detect gadolinium deposition in brain tissue.…”
Section: Introductionmentioning
confidence: 92%